Degradation and interconversion of plant pteridines during sample preparation and ultra-high performance liquid chromatography–tandem mass spectrometry. (1st March 2016) - Van Daele, Jeroen; Blancquaert, Dieter; Kiekens, Filip; Van Der Straeten, Dominique; Lambert, Willy E.; Stove, Christophe P.
Highlights: Literature contains conflicting data regarding interconversion, degradation and quantitation of pterins. Behavior of spiked and endogenous plant pterins during sample preparation was studied. Pterin interconversion and degradation patterns during UHPLC–MS/MS analysis were documented. A sample preparation protocol for the UHPLC–MS/MS determination of selected plant pterins was drafted. Abstract: The degradation and interconversion of a selected set of pterins (dihydroneopterin, hydroxymethyldihydropterin, dihydroxanthopterin, neopterin, hydroxymethylpterin, xanthopterin, 6-formylpterin, 6-carboxypterin and pterin), spiked to charcoal-treated potato and Arabidopsis thaliana matrix was investigated, together with their relative recovery in potato and A. thaliana . As a result, a matrix-specific procedure for the ultra-high performance liquid chromatography–tandem mass spectrometry based determination of 6 aromatic pterins (neopterin, hydroxymethylpterin, xanthopterin, 6-formylpterin, 6-carboxypterin and pterin) is proposed: 1.5 ml of an N2 -flushed, alkaline (pH = 10) extraction solvent is added to 200 mg of plant sample. After boiling and homogenization, the samples are incubated: Arabidopsis samples for 30 min at room temperature, while shaking, and potato samples for 2 h at 37 °C (applying a dienzyme treatment with α-amylase and protease). After a final boiling step, the samples are ultrafiltrated and resulting extracts are analyzed by UHPLC–MS/MS.